Strategic procurement :organizing suppliers and supply chains for competitive advantage - Booth, Caroline, 1958- (London Kogan Page, 2010)
"Most organizations, regardless of industry, spend more money on suppliers than they do on employing their staff. Written for the non-procurement expert, Strategic Procurement explores the "why" and "what" of good procurement rather than the "how." It explains the importance of focusing efforts on this previously neglected area of business where P&L impact is relatively painless and immediate, where benefit to cost ratios of 10-to-1 are realistic ambitions and in-year payback is possible. This expanded edition includes new chapters on mergers & acquisitions, supplier-related risk management and global supply. All case studies are updated and vital information has been added to chapters on corporate responsibility, procurement strategies and supplier collaboration. Strategic Procurement shows how to cut costs without harming a business and emphasizes the importance of supplier relationship management, making it a valuable resource for understanding of the true worth of procurement in the boardroom. "--
"Most organizations, regardless of industry, spend more money on suppliers than they do on employing their staff. Written for the non-procurement expert, Strategic Procurement explores the 'why' and 'what' of good procurement rather than the 'how.' It explains why you should focus your efforts on this previously neglected area of business and rich rewards, where P&L impact is relatively painless and immediate, where benefit to cost ratios of 10 to 1 are realistic ambitions and in-year payback is possible. This new expanded edition covers all the aspects of strategic procurement, with new chapters on: -Mergers & acquisitions -Supplier-related risk management -Global supply All case studies are updated and Caroline has added vital new information to her chapters on corporate responsibility, good procurement across the organisation and new ways of supplier collaboration. Showing you how to cut costs without harming your business and the importance of recognizing supplier relationship management, Strategic Procurement offers real understanding of the true worth of procurement in the boardroom"--
Includes bibliographical references (pages 203-205) and index.
Keywords: Industrial procurement; Business logistics; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Purchasing & Buying; BUSINESS & ECONOMICS / Distribution